2010
DOI: 10.1007/s00410-010-0506-2
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth and high field strength element partitioning between iron-rich clinopyroxenes and felsic liquids

Abstract: Rare earth elements are commonly assumed to substitute only for Ca in clinopyroxene because of the similarity of ionic radii for REE 3+ and Ca 2+ in 8-fold coordination. The assumption is valid for Mg-rich clinopyroxenes for which observed mineral/melt partition coefficients are readily predicted by the lattice strain model for substitution onto a single site (e.g. Wood and Blundy, 1997). We show that natural Fe-rich pyroxenes in both silica-undersaturated and -oversaturated magmatic systems deviate from this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 61 publications
(75 reference statements)
5
34
0
Order By: Relevance
“…Tiepolo et al (2000), they and Blundy and Wood (2003) in fact propose that the ionic radius of Ta 5+ is 0.01 -0.02 Å smaller that that of Nb 5+ . Olin and Wolff (2010) however showed that Y 3+ cpx/melt partitioning deviates from that of the HREE to an extent that the LSM cannot explain unless the Shannon (1976) value of the ionic radius for Y 3+ is grossly in error. Fasnia titanite displays similar behavior to a greater degree (Figs.…”
Section: Factors Other Than Cation Charge and Radius: Y/ho Zr/hf Nb/tamentioning
confidence: 92%
See 4 more Smart Citations
“…Tiepolo et al (2000), they and Blundy and Wood (2003) in fact propose that the ionic radius of Ta 5+ is 0.01 -0.02 Å smaller that that of Nb 5+ . Olin and Wolff (2010) however showed that Y 3+ cpx/melt partitioning deviates from that of the HREE to an extent that the LSM cannot explain unless the Shannon (1976) value of the ionic radius for Y 3+ is grossly in error. Fasnia titanite displays similar behavior to a greater degree (Figs.…”
Section: Factors Other Than Cation Charge and Radius: Y/ho Zr/hf Nb/tamentioning
confidence: 92%
“…As described above, magmatic processes have scrambled crystals and glasses in the compositionally variable Fasnia phonolite, precluding confident identification of mineralglass pairs based on visual criteria. The method used by Olin and Wolff (2010) and outlined below is independent of major element mineral compositions, assumes that the LSM is a good first-order predictor of trace element partition coefficients, and does not rely on textural relationships.…”
Section: Partition Coefficientsmentioning
confidence: 99%
See 3 more Smart Citations